2015
DOI: 10.1186/s13039-015-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Familial intragenic duplication of ANKRD11 underlying three patients of KBG syndrome

Abstract: BackgroundKBG syndrome, a rare autosomal disorder characterised by distinctive craniofacial and skeletal features and developmental delay, is caused by haploinsufficiency of the ANKRD11 gene.ResultsHere we describe two siblings with multiple symptoms characteristic of KBG and their mother with a milder phenotype. In the siblings, array-based comparative genomic hybridization (array CGH) identified an intragenic microduplication affecting ANKRD11 that was absent from the parents’ array CGH profiles. Microsatell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…almost 200 individuals have been reported in the medical literature, but it is likely that KBG syndrome is underdiagnosed because many of its features, including ID, are often mild, and none of the features are a prerequisite for the diagnosis [Sirmaci et al, 2011;Crippa et al, 2015].…”
mentioning
confidence: 99%
“…almost 200 individuals have been reported in the medical literature, but it is likely that KBG syndrome is underdiagnosed because many of its features, including ID, are often mild, and none of the features are a prerequisite for the diagnosis [Sirmaci et al, 2011;Crippa et al, 2015].…”
mentioning
confidence: 99%
“…The Exome Aggregration Consortium (ExAC) probability of loss-of-function (LOF) intolerance (pLI) score was calculated to be 1.0, indicating that this gene is very intolerant to mutations, and previous studies have indicated that mutations in this gene often lead to haploinsufficiency (see Discussion) (Lek et al 2016b). Other mutations in this gene have been previously identified as contributing to KBG syndrome, a rare disease that affects around 60 to 70 people worldwide (Brancati et al 2006; Sirmaci et al 2011; Crippa et al 2015; Walz et al 2015). The presence of the mutation was confirmed using Sanger sequencing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More than 100 cases have now been reported (see Fig. 6; Ockeloen et al 2015; Goldenberg et al 2016); however, it is likely that KBG syndrome is underdiagnosed because dysmorphic features may be underreported, subtle, or even nonexistent, and cognitive delay can vary from mild to moderate (Crippa et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Height SDS of 72 patients with ANKRD11 aberration (Crippa et al, ; Goldenberg et al, ; Isrie et al, ; Li et al, ; Novara et al, ; Ockeloen et al, ; Reynaert et al, ; Sirmaci et al, ; Walz et al, ; Xu et al, ). The height of 42 patients below −2.0 SD account for 58% of 72 total.…”
Section: Discussionmentioning
confidence: 99%